FENOMENA KEBEBASAN BEREKSPRESI DI INSTAGRAM - Hardina, Andhika Febi (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2021)
ABSTRACT Instagram is one of the platforms that is widely used by the public for freedom of expression. However, the term freedom itself gets a lot of perceptions so that many issues are against ethics and norms. Some elements cover themselves in a word "freedom". In this paper, the author wants to explain about freedom of expression, the limits of freedom, and how the phenomena relating to freedom of expression. The author concludes that the freedom of expression that crosses the boundaries of ethics and norms, seems to make a feeling of losing control in expressing his feelings and thoughts. Each individual should have full rights and obligations to use social media intelligently and with full responsibility.